Pengaruh Reputasi Koperasi terhadap Kepercayaan Anggota Koperasi - Mukhammad Ridwan; Agus Arifin; Itah Bella Permana; Euis Widianti; Iva Lathifah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
The importance of loyalty from all members to the cooperative by paying attention to the reputation of the cooperative and the trust of its members. The purpose of this study was to find out how the influence of Cooperative Reputation (X) on Cooperative Member Trust (Y) in the KSU TandangSari Sumedang dairy farming business unit. This research is quantitative research. The population is all members of the business unit dairy farmer KSU Tandangsari Sumedang, using a random sampling method involving 42 respondents. Data collection uses questionnaires (questionnaires) and interviews with answers based on the guttman scale "YES" or "NO". Data analysis using correlation regression analysis with previous hypothesis testin. The results of this study indicate that the reputation of cooperatives has a strong influence on the trust of cooperative members in the KSU TandangSari Sumedang dairy farming business unit.